2014
DOI: 10.1128/jvi.00257-14
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Nucleocytoplasmic Transport of H1N1 Influenza A Virus Nuclear Export Protein

Abstract: The influenza A virus nuclear export protein (NEP) plays crucial roles in the nuclear export of the viral ribonucleoprotein complex through the chromosome region maintenance 1 (CRM1)-mediated cellular protein transport system. However, the detailed mechanism of NEP nucleocytoplasmic trafficking remains incompletely understood. Here, we investigated the subcellular localization of NEP from two strains of H1N1 influenza A virus and found that 2009 swine-origin H1N1 influenza A virus A/California/04/2009 (CA04) N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…In addition, we have also found that the CA04 strain displays different vRNP distribution patterns, forming unique nuclear aggregates, with respect to WSN by comparing different strains of H1N1 NEP for vRNP nuclear translocation. In the further study, we confirmed that CA04 NEP interacts less efficiently with CRM1 and site T48 is responsible for the nuclear aggregation [ 44 ]. In view of NEP playing an important role in viral polymerase activity and vRNP nuclear transport efficiency, these differences may be one reason for divergence of the pathogenicity and host adaptation range between these virus strains.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In addition, we have also found that the CA04 strain displays different vRNP distribution patterns, forming unique nuclear aggregates, with respect to WSN by comparing different strains of H1N1 NEP for vRNP nuclear translocation. In the further study, we confirmed that CA04 NEP interacts less efficiently with CRM1 and site T48 is responsible for the nuclear aggregation [ 44 ]. In view of NEP playing an important role in viral polymerase activity and vRNP nuclear transport efficiency, these differences may be one reason for divergence of the pathogenicity and host adaptation range between these virus strains.…”
Section: Discussionmentioning
confidence: 73%
“…It may not need a NLS as it is only 14 kDa in size, and at present, no NLS has been found in NEP. Through the use of an inhibitor of NLS-dependent active nuclear transport and an energy depletion assay, it was demonstrated that NEP enters the nucleus by passive diffusion [ 44 ].…”
Section: Nucleocytoplasmic Shuttling Mechanism Of Iav Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting RNP export modality was discovered while investigating mRNA export in Influenza A viruses (IAV) [ 138 ]. Electron microscopy studies show that IAV enlarges the nuclear pores in infected cells by around 20 nm (a final size of around 50 nm) [ 139 , 140 ] ( Figure 4 ). The increase in pore diameter facilitates the translocation of large protein complexes.…”
Section: Other Exits For Mrnamentioning
confidence: 99%
“…, , Gao et al . , ). The NP of the WSN strain contains a CRM1‐dependent NES and two CRM1‐independent NESs, which are crucial for nuclear export (Yu et al .…”
Section: Introductionmentioning
confidence: 97%